(untitled) (Journal of Basic and Applied Research in Biomedicine, 2024)
Plants do not only serve as a source of food, but, also as a source of shelter, clothing and more importantly as a source of medicines for the treatment of diseases due to their therapeutic virtues. Plants like Xylopia aethiopica otherwise known as Negro pepper or African is used traditionally to treat several diseases and as food and spice in most African countries. It is of public interest to scientifically verify its toxicity and health benefits of this plant. The aim of this study was to investigate the effect of the administration of the leaves and fruits (with and without seeds) extracts of X. aethiopica on haematological parameters in Wistar Rats. The Wistar rats were administered with 125 mg/kg, 250 mg/kg, 500 mg/kg of hydro-ethanolic extracts of the leaves, fruits with seeds and fruits without seeds extracts by oral gavage for 30 days, 60 days and 90 days while the control group received feeds and water ad libitum. After the treatment periods, rats were sacrificed by cervical dislocation and blood collected by cardiac puncture. Full blood count was conducted using Automated Haematology analyser. Data were compared using analysis of variance (ANOVA) and a p-value of 0.05 was considered significant. The haemoglobin (Hb) level (p =0.46) and packed cell volume (PCV) (p =0.23) of the rats were not significantly different from controls. But, mean white blood cell count (WBC) (p =0.01) and platelet count (PLT) (p =0.01) were significantly increased in a dose dependent manner after three months’ treatment. The mean WBC was significantly higher amongst the female rats, while mean platelet was higher amongst the male rats when compared with the controls. There was sex dependent increases in WBC and platelet counts among Wistar rats.